The focal mechanism and field investigations of mining-induced earthquake by super-thick and weak cementation overburden strata fracturing - Xianxi Bai; Anye Cao; Changbin Wang; Yaoqi Liu; Chengchun Xue; Xu Yang; Yao Yang; Songwei Wang; Qi Hao (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract Mining-induced earthquake (MIE) is a non-natural earthquake induced by mining activities. In Ordos mining area, super-thick and weak cementation overburden strata (STWCS) are common occurrence in Jurassic coal seam overlying strata. To explain and quantify the focal mechanism and roof fracture characteristics of MIE under the STWCS, the surface subsidence, ground borehole televiewer imaging and microseismic monitoring technologies were used to observe the fracturing of STWCS. The relative moment tensor method was also used to explore quantify focal mechanism of MIE. The results show that the development height of rock fractures increases, and the STWCS start to break when the panel below retreats along goafs. During this period, the surface stepped subsidence increases rapidly, and MIEs with magnitude above 2.0 begin to appear. The inversion matrix is constructed with the relative moment tensor method to solve the source mechanism of coal mining microearthquakes. The matrix improves the inversion efficiency and accuracy, thus being suitable for solving the focal mechanism of MIE by roof breaking. When coal seam is mined under the STWCS, the dip angle of focal rupture surface is mainly between 0° and 30°, accounting for about 50% of the total. The seismic source is mainly featured with roof horizontal separation tension and roof rotation compression instability. During mining along goafs, the seismic sources displayed a tendency of upward expansion and the shear slip ruptures were more than that in the solid coal mining stage. The focal mechanism of the MIEs in Shilawusu Coal mine was caused by the primary and periodic tension rupture of the STWCS and shear slip rupture. With the continuous mining of the panel, there is still the possibility of another round of MIEs. The research results provide a reference for the prediction, risk assessment and disaster control of MIEs under extremely thick overburden strata.